The Resilient Thread: Digital Archiving and the Semantic Revitalization of Palembang's Songket Weaving Traditions - Dian Rahayu; Iqbal Anugerah; Henry Peter Paul (Enigma in Cultural, 2024)
Palembang's Songket, a UNESCO-recognized Intangible Cultural Heritage, faces significant threats from modernization and the gradual erosion of its tacit knowledge, particularly the philosophical meanings embedded within its motifs. This study addressed the urgent need for a preservation model that transcends simple digitization by focusing on semantic revitalization. This research employed a multi-phase, mixed-methods approach conducted between 2023 and 2025. We developed a comprehensive digital archive through high-resolution photogrammetry of 150 heritage Songket textiles and ethnographic fieldwork, including in-depth interviews with 15 master weavers in Palembang. A bespoke semantic ontology was constructed using Web Ontology Language (OWL) to map the complex relationships between motifs, techniques, materials, and their socio-cultural meanings. This ontology formed the backbone of an interactive web-based platform, "The Songket Legacy," which was subsequently evaluated through a user engagement study with 50 participants from diverse backgrounds, including weavers, designers, and students. The project resulted in a robust digital archive containing over 50 gigabytes of data. The Songket Semantic Ontology successfully defi ned 75 distinct motifs and established over 400 relational assertions, linking visual patterns to their historical narratives and philosophical underpinnings. The user engagement study yielded a high System Usability Scale (SUS) score of 85.5. Qualitative feedback confirmed that the semantic framework significantly enhanced users' understanding and appreciation of Songket, with 92% of participants reporting an increased ability to interpret motif symbolism. In conclusion, this study demonstrated that a semantic-web approach offers a powerful methodology for the revitalization of intangible cultural heritage. By creating a "living" digital archive that makes tacit knowledge explicit and accessible, this project provides a scalable model for preserving and promoting the cultural legacy of Palembang's Songket for future generations, fostering both cultural continuity and creative innovation.